2020
DOI: 10.1002/btpr.2972
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the NADPH pool for xylitol production using recombinant Saccharomyces cerevisiae

Abstract: Xylitol is a five‐carbon sugar alcohol that has a variety of uses in the food and pharmaceutical industries. In xylose assimilating yeasts, NAD(P)H‐dependent xylose reductase (XR) catalyzes the reduction of xylose to xylitol. In the present study, XR with varying cofactor specificities was overexpressed in Saccharomyces cerevisiae to screen for efficient xylitol production. Xylose consumption and xylitol yields were higher when NADPH‐dependent enzymes (Candida tropicalis XR and S. cerevisiae Gre3p aldose reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Unlike the unwanted occurrence of xylitol as a by-product in bioethanol production from pentoses described above, xylitol is of value as a sweetener and a functional food additive, with proposed anticancerogenic effects. Heterologous expression of xylose reductase genes has been employed in this context for xylitol production in yeast [ 120 ].…”
Section: Biotechnological Implicationsmentioning
confidence: 99%
“…Unlike the unwanted occurrence of xylitol as a by-product in bioethanol production from pentoses described above, xylitol is of value as a sweetener and a functional food additive, with proposed anticancerogenic effects. Heterologous expression of xylose reductase genes has been employed in this context for xylitol production in yeast [ 120 ].…”
Section: Biotechnological Implicationsmentioning
confidence: 99%
“…Although the recombinant strain produced no acetate (and consequently the pH of the medium dropped just to pH 4.5) and less xylitol and ethanol, the production of glycerol was only slightly increased ( Figure 2, Table 6), indicating that other factors may limit xylose utilization by our engineered yeast strains. For example, the bottleneck may be a consequence of the relatively low affinity of the cloned SpXYL2.2 xylitol dehydrogenase for both NAD + and xylitol (Table 4), or the intracellular pools of reduced or oxidized and NADH/NADPH ratio of co-substrates [49,50], or even the low affinity of yeast sugar permeases for xylose transport [5,14,51]. Nevertheless, the ASY-2 strain transformed with the pPGK-SaXYL1 and pTEF-SpXYL2.2 plasmids (Table 6) showed xylitol yields (Y p/s = 0.614 g xylitol/g xylose) and volumetric productivities (Q p = 0.513 g/L/h) as good as or superior to those reported by other naturally xylose fermenting yeasts [52][53][54][55] or even engineered S. cerevisiae strains [38,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the bottleneck may be a consequence of the relatively low affinity of the cloned SpXYL2.2 xylitol dehydrogenase for both NAD + and xylitol (Table 4), or the intracellular pools of reduced or oxidized and NADH/NADPH ratio of co-substrates [49,50], or even the low affinity of yeast sugar permeases for xylose transport [5,14,51]. Nevertheless, the ASY-2 strain transformed with the pPGK-SaXYL1 and pTEF-SpXYL2.2 plasmids (Table 6) showed xylitol yields (Y p/s = 0.614 g xylitol/g xylose) and volumetric productivities (Q p = 0.513 g/L/h) as good as or superior to those reported by other naturally xylose fermenting yeasts [52][53][54][55] or even engineered S. cerevisiae strains [38,49,50]. It is important to note that the maximal expected theoretical yield for the biotransformation of xylose into xylitol is 0.905-0.917 g xylitol/g xylose consumed, depending on how the cells will regenerate the NADH/NADPH consumed in the reduction of xylose, and that no carbon is used for cell growth or production of other metabolites [56].…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been reported that accessory enzymes from hypercellulolytic Penicillium funiculosum facilitate the complete saccharification of sugarcane bagasse [39]. sugarcane bagasse [41,42]. In previous work, Vallejos et al [14] reported maximal xylitol concentration (32.0 g L -1 ) from hemicellulosic liquors obtained from sugarcane bagasse autohydrolysis using Candida tropicalis (104.1 g L -1 xylose, 0.46 g g -1 yield, 0.27 g L -1 h -1 productivity).…”
Section: Hydrogenation Of Xylose-rich Liquors To Obtain Xylitolmentioning
confidence: 99%